(untitled) (London, 1993)
This book represents both for the scholar and the students an updating and a perspective of value on a subject - language and learning - that is at the heart of the educational process. Each contribution sharpens our appreciation of how fully learning depends on language of all kinds, spoken, written, heard and seen, and particularly for the most dependent - the young, the culturally deprived and the poorly educated
Keywords: Language and education,Sociolinguistics; Adresses, essays, lectures,Adresses, essays, lectures